ETIKA SOSIAL SANTRI MENUJU MODERNISASI PENDIDIKAN(TELAAH PENDIDIKAN SANTRI DI KUDUS) - Nasir, Amin (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
Pesantren world faced with the problems of globalization, which can be assured to contain responsibility which is not light for pesantren. Increasingly, the challenge of the pesantren world is getting bigger and harder in the present and future. The paradigm of "maintaining a long, relevant legacy and picking up the latest thing better" needs to be reflected back. Pesantrens should be able to intelligently clarify our contemporary problems with contemporary approaches. On the other hand, modernity, which some say must be done by pesantren, contains the paradigms and worldviews that have changed the old worldview to the world itself and man. but did not rule out there is still potential that can be developed for the present. One of the things that need to be modified is the pesantren education system. Traditional learning systems, namely sorogan, bandongan, balaghan, or halaqah should begin to be balanced with the modern learning system. In the aspect of the curriculum, pesantren should also accommodate the curriculum of the government and the campus system and follow the modernization of leading university education.Keywords:Ethics Social, Student, Modernization of Education